2023
DOI: 10.1111/nph.19121
|View full text |Cite
|
Sign up to set email alerts
|

Rhizophagus irregularis, the model fungus in arbuscular mycorrhiza research, forms dimorphic spores

Abstract: Summary Rhizophagus irregularis is the model species for arbuscular mycorrhizal fungi (AMF) research and the most widely propagated species for commercial plant biostimulants. Using asymbiotic and symbiotic cultivation systems initiated from single spores, advanced microscopy, Sanger sequencing of the glomalin gene, and PacBio sequencing of the partial 45S rRNA gene, we show that four strains of R. irregularis produce spores of two distinct morphotypes, one corresponding to the morphotype described in the R. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…The life history of arbuscular mycorrhizal fungi provides further insights. Sporulation of the model fungus Rhizophagus irregularis yields spores of two different morphologies, including those matching the phenotypes of Rhizophagus fasciculatus in the case of at least four isolates, as described by Kokkoris et al (2024). Lofgren et al (2024Lofgren et al ( , in this issue pp.…”
Section: Life History Traits Of (Invasive) Mycorrhizal Fungimentioning
confidence: 92%
“…The life history of arbuscular mycorrhizal fungi provides further insights. Sporulation of the model fungus Rhizophagus irregularis yields spores of two different morphologies, including those matching the phenotypes of Rhizophagus fasciculatus in the case of at least four isolates, as described by Kokkoris et al (2024). Lofgren et al (2024Lofgren et al ( , in this issue pp.…”
Section: Life History Traits Of (Invasive) Mycorrhizal Fungimentioning
confidence: 92%
“…The sporulation we observed in openings of the chip design visibly clogged passages and would have prevented any movement of organisms, water or gas across to the adjacent pore space. Irregularly shaped spores of R. irregularis have been documented in soils, including variable globose, oblong and irregular, sometimes even knobby shapes (INVAM, Walker, 2013) and a recent discovery has showed that R. irregularis spores may be dimorphic (Kokkoris et al, 2023). While it is recognised that different AMF species produce a wide diversity of spore shapes and sizes (Smith and Read, 2008;Aguilar-Trigueros et al, 2019), the potential implications of spores being formed into the shape of the micro scale environment has not previously been examined.…”
Section: Amf Habitat Modificationmentioning
confidence: 99%
“…Compared to 45S sequences, the taxonomic resolution of the rpb1 sequences is higher, and their use reduces the risk of creating potential phylogenetic artifacts due to paralogous sequences because rpb1 is a single-copy gene in arbuscular mycorrhizal fungi (Stockinger et al, 2014 ). Other single-copy marker loci recommended for use in reconstructing AMF phylogenies are the ß -tubulin and glomalin genes (Corradi et al, 2004a , b ; Msiska and Morton, 2009 ; Magurno et al, 2019 ; Kokkoris et al, 2023 ). However, lower resolution and poor support at the order level of the ß -tubulin phylogenies, compared to those reconstructed from SSU, LSU, and rpb1 sequences (Msiska and Morton, 2009 ) and the relatively small number of sequences for the AMF glomalin gene (Magurno et al, 2019 ; Kokkoris et al, 2023 ), have made these two protein-coding loci of little use in taxonomic analyses of large numbers of Glomeromycota representatives.…”
Section: Introductionmentioning
confidence: 99%